Peran Surveyor Kadaster Berlisensi pada Pendaftaran Tanah Sistematik Lengkap - Wahanisa, Rofi; Sumerta Yasa, Putu Gede Arya; Adiyatma, Septhian Eka (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2024)
Land registration is a crucial component in Indonesia for registering land rights and collecting land parcel data. Issues that often arise in the context of land registration include measurement errors, boundary disputes, and the absence of neighboring landowners. Considering the objectives of land registration, which include creating legal certainty, providing information to relevant parties, and maintaining administrative order, the importance of carrying out land registration to create legal clarity and facilitate efficient land administration is emphasized. Through the Nawacita, the acceleration of the land registration program is known as the Complete Systematic Land Registration (PTSL). The research method used is a normative juridical approach, complemented by literature studies and supporting data from interviews. Measurement becomes an important stage in land registration, as it is the initial stage of collecting physical and juridical data that is crucial for the subsequent stages of the land registration process. Errors or carelessness in this stage can potentially lead to disputes in the future. However, the available human resources for measurement do not meet the measurement target. As a result, the licensed cadastral surveyor profession has emerged. This paper discusses and analyzes the role and obstacles of licensed cadastral surveyors in PTSL. The research method is carried out with a normative juridical approach, using primary literature data and journals to analyze the role and obstacles of licensed cadastral surveyors in the implementation of PTSL. Pendaftaran tanah merupakan komponen krusial di Indonesia untuk mendaftarkan hak atas tanah dan mengumpulkan data bidang tanah. MPersoalan dalam konteks pendaftaran tanah yang seringkali muncul antara lain, salah pengukuran, sengketa batas, maupun ketidakhadiran pihak yang tanahnya berbatasan. Jika ditilik dari tujuan pendaftaran tanah antara lain menciptakan kepastian regulasi/hukum, memberikan informasi untuk pihak-pihak terkait, dan menjaga ketertiban administrasi. Melalui Nawacita program percepatan dilakukan dengan pendaftaran tanah sistematis lengkap. Menggunakan metode penelitian yuridis normatif, dilengkapi dengan studi pustaka dan data pendukung dari hasil wawancara. Pengukuran menjadi tahapan dari pendaftaran tanah yang penting, karena dalam tahap merupakan tahap awal pengumpulan data yang bersifat fisik dan data yang bersifat yuridis yang sangat penting pada proses pendaftaran tanah tahap selanjutnya. Karena dalam tahap ini adalah tahap awal untuk menentukan posisi/ letak dari tanah yang akan di daftar, kesalahan/ ketidak hati-hatian dalam proses ini nantinya akan sangat mungkin memunculkan sengketa di kemudian hari. Namun, dalam kenyataanya jumlah sumber daya manusia (SDM) dalam pengukuran belum memenuhi untuk pemenuhan target pengukuran. Oleh karena itulah memunculkan profesi surveyor kadaster berlisensi. Dalam tulisan ini akan dibahas dan dianalisa tentang peran dan hambatan surveyor kadaster berlisensi dalam PTSL Metode penelitian ini dilakukan dengan pendekatan yuridis normative, dengan penggunaan data primer literatur, jurnal yang dipergunakan untuk menganalisa peran dan hambatan dari surveyor kadaster berlisensi dalam pelaksanaan PTSL.